2016
DOI: 10.1016/j.ejphar.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypothalamic-Pituitary-Adrenal axis and corticotropin-releasing factor stress system on cue-induced relapse to alcohol seeking

Abstract: A large body of evidence has shown that the Corticotropin Releasing Factor (CRF) system, which plays a key role in stress modulation, is deeply involved in relapse to alcohol seeking induced by exposure to stressful events such as foot shock or yohimbine injections. Exposure to environmental cues is also known to be a trigger for alcohol relapse, nevertheless, the relationship between the relapse evoked by the cue-induced model and the CRF stress systems remains unclear. The purpose of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…These studies highlight the complex interactions between gender, stress disorders, and alcoholism. In fact, alcoholism can be considered a stress-related disorder as stress systems are disrupted in the transition from casual alcohol use to alcohol dependence (Galesi et al, 2016; Koob, 2013; Seo and Sinha, 2014). Once in this dependent state, hypersensitive stress systems cause negative affective withdrawal symptoms which drives further drinking to alleviate these symptoms (Koob, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies highlight the complex interactions between gender, stress disorders, and alcoholism. In fact, alcoholism can be considered a stress-related disorder as stress systems are disrupted in the transition from casual alcohol use to alcohol dependence (Galesi et al, 2016; Koob, 2013; Seo and Sinha, 2014). Once in this dependent state, hypersensitive stress systems cause negative affective withdrawal symptoms which drives further drinking to alleviate these symptoms (Koob, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of CORT on alcohol consumption were not determined in the present study; however, the results detected a positive correlation between the two factors. Previous studies have revealed that the interaction between CORT and the dopaminergic system in the nucleus accumbens may facilitate the reinforcing effects of alcohol and other drugs (45)(46)(47). Therefore, CART 55-102 may serve an inhibitory role in drinking behavior through the disruption of excessive CORT serum levels; however, more evidence is required from future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, cue-induced reinstatement of alcohol seeking was not blocked by a non-specific peptide CRFR antagonist that targeted both CRFR1 and CRFR2 (Liu and Weiss 2003). But a more recent study suggests that CRFR1 might play a role in cue-induced reinstatement; that study showed that rats treated with a systemic CRFR1 antagonist respond less on an alcohol-paired lever after presentation of an alcohol-paired cue, relative to vehicle-treated rats (Galesi et al, 2016). This effect may be mediated by hypothalamic CRF signaling, because systemic CRFR1 antagonist effects were mimicked by systemic injection of metyrapone, a glucocorticoid synthesis inhibitor (Galesi et al 2016).…”
Section: 4 Brain Region-specific Crfr1 and Crfr2 Effects On Alcoholmentioning
confidence: 99%
“…But a more recent study suggests that CRFR1 might play a role in cue-induced reinstatement; that study showed that rats treated with a systemic CRFR1 antagonist respond less on an alcohol-paired lever after presentation of an alcohol-paired cue, relative to vehicle-treated rats (Galesi et al, 2016). This effect may be mediated by hypothalamic CRF signaling, because systemic CRFR1 antagonist effects were mimicked by systemic injection of metyrapone, a glucocorticoid synthesis inhibitor (Galesi et al 2016). More studies are needed to clarify these apparently contradictory results, and to clarify the potential role for hypothalamic and extra-hypothalamic CRF signaling in cue-induced reinstatement of alcohol seeking.…”
Section: 4 Brain Region-specific Crfr1 and Crfr2 Effects On Alcoholmentioning
confidence: 99%